Devarattam - A Historical View - Karthikeyan, P (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2025)
Folk dances are the gateways that reveal the Tamil tradition, the way of life of the people and the cultural roots of the land. The main occupation of these people is hunting. Through this game, we can see how the human body works while hunting. Devarattam is performed as a ritual event, not as a recreational game or a professional game to please people. When we say Devarattam, we tend to associate it with the caste of gods. Devarattam has no connection with the Devarina people. Most of the rituals that take place in the life of the carpet weavers are performed outside the village. This place is called Mandhai or Kottaimedu. The ritual of building a hut in the flower ceremony held in the Kambalathu Nayak community and the ritual on the 16th day of bringing the flower-covered woman home from the herd are notable. Musically arranged sounds and body movements like Parinamitra are given the names of dance and atam. The original poetry composed by man under the inspiration of his poetic sense is presented as dance. Devarattam is a social activity of the Sumpanathars, which has a unifying effect that unites all the members of the community. It also has a collective effect that unites the individual with the community and has a wide platform where even a hundred people can dance together at the same time. Devarattam is characterized by its freedom, simple control, and attracts and captivates everyone.